Sustainable frameworks in the chemical sector - Afaneh, Mazen (2021)
This research investigates 30 global chemical companies in order to understand their sustainability frameworks using the Hart and Milstein model. Sustainability is considered as a major factor that provide value creation to companies through three major aspects which are higher capital returns, better risk management, and company growth. The integration of sustainability in the companies’ corporate strategies is seen to increase in the past decade with the emergence of United Nations Sustainable Development Goals, the United Nations Environment Programme Finance Initiative, and the Paris Climate Agreement. The changing requirements by governments globally with regards to carbon footprint and greenhouse gas emissions are pushing companies to revisit the implications of their operations on the environment as there are different methods which governments enforce these environmental protection laws through taxes, green incentives & subsidies, and fines. Companies are also paying close attention to their triple bottom lines which include social, environmental and economical issues where they aim to provide added value to these lines and their stakeholders. Company employees are considered the first social priority for these chemical companies as they strive to provide a better and safer working environment for their employees while caring for their wellbeing and professional development.